Preoperative Measurement Using VIDEO-PHOROMETRY and Surgical Results - Murai, Ami; Yamagishi, Tomoko; Hatsukawa, Yoshikazu; Nimi, Akiko; Kawamura, Hirohisa (JAPANESE ORTHOPTIC JOURNAL, 1997)
Preoperative measurement of ocular deviations were performed using VIDEO-PHOROMETRY on 39 esotropia patients. The amount of surgery needed was determined by the measurements of the VIDEO-PHOROMETRY as well as the alternative prism cover test (APCT) or the Krimsky test. The VIDEO-PHOROMETRY was successfully performed on all the subjects. Measurements of 32 patients using the VIDEO-PHOROMETRY closely coincided with those made by APCT and the Krimsky test. One week postoperative deviations ranged from 4 prism diopters exo- to 14 prism diopters eso-deviations. VIDEO-PHOROMETRY at 1.4m was useful in cases of infantile esotropia with convergence excess. Fixation, latent deviation wearing glasses and head position may affect the results when measuring with VIDEO-PHOROMETRY.